A Framework for Price Statistics - Zieschang, Kimberly (Washington, D.C. : International Monetary Fund, 2000)
This paper describes the primary framework associating the four principal price indices in the system of economic statistics-the Producer Price Index (PPI), the Consumer Price Index (CPI), and the Export and Import Price Indices (XPI and MPI)-with the macroeconomic value aggregates they decompose into price and volume components. The paper begins by defining the basic algebra of price indices. It then discusses the definition of the value aggregates comprising the goods and services components of the System of National Accounts 1993 (1993 SNA). The paper concludes by briefly considering purchasing power parities and labor compensation indices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet